Effects of Mimosa pudica L. leaves extract on anxiety, depression and memory - Ganesh Patro; Himanshu Sahoo; Bijay Kumar Mohanty (Mashhad University of Medical Sciences, 2016)
Objective: The present study was carried out to investigate the neuropharmacological activities of ethyl acetate extract of Mimosa pudica (EAMP) leaves on anxiety, depression and memory in a mouse model. Materials and Methods: Anti-anxiety potential of EAMP was evaluated by elevated plus maze (EPM), light-dark box (LDB) and social interaction (SI) tests in mice.Anti-depressant potential of EAMP was evaluated by forced swimming (FST), tail suspension (TST), and open field tests (OFT). The behavioral findings were further corroborated with estimation of neurotransmitters and their metabolites from mouse brain homogenate. Effect on learning and memory was evaluated by EPM, passive avoidance (PA) tests. Further, it was confirmed with assessment of acetylcholinesterase and caspase-3 activity in brain homogenate. Results: EAMP showed significant anti-anxiety activity by increasing the time spent in open arm of EPM, light box of LDB. Social interaction time was increased significantly (p